Boosting Young EFL Learners' English Vocabulary Acquisition by Utilizing Puppet Pictures as Storytelling Media - Brilianti, Amalia Eka; Sugirin, Sugirin (Universitas Muhammadiyah Yogyakarta, 2000)
Students' interest becomes the most important aspect of successful teaching and learning. One way to attract students' interest in participating in the lesson is by using fun learning media like puppet pictures. This study explores how employing puppet pictures as a storytelling and sharing medium can improve students' vocabulary acquisition. The present study employed a pre-experimental approach to assess the vocabulary proficiency level achieved through puppet image storytelling media. The group, which had a pre-test and post-test, was considered a single sample for teaching using puppet visuals and storytelling medium. The research subjects consisted of first-grade students enrolled at Ariya Metta Elementary School. The evaluation instruments utilized consisted of a pre-test and post-test, designed based on phase A of the Merdeka curriculum. These instruments were employed to evaluate the enhancement or notable increase in vocabulary scores, employing puppet image narrative media. The pre-test and post-test data were calculated using a statistical analysis program. The data statistics from the descriptive analysis and matched sample statistics showed that the average score of the pre-test (57.86) increased to the post-test score (88.57). In addition, the paired sample T-test yielded a p-value of 0.000, less than the significance level of 0.05. The result indicates that the Null Hypothesis (Ho) was rejected, and the alternative hypothesis (Ha) was accepted. Ultimately, puppet storytelling media had a significant impact on enhancing pupils' vocabulary development.